Effects of music therapy on occupational stress and burn-out risk of operating room staff. Issue 1 (1st January 2020) - Kacem, I.; Kahloul, M.; El Arem, S.; Ayachi, S.; Hafsia, M.; Maoua, M.; Ben Othmane, M.; El Maalel, O.; Hmida, W.; Bouallague, O.; Ben Abdessalem, K.; Naija, W.; et al.
ABSTRACT: The operating theatre staff is exposed to various constraints such as excessive working hours, severe medical conditions and dreadful consequences in case of malpractice. These working conditions may lead to high and chronic levels of stress, which can interfere with medical staff well-being and patients quality of care. The aim of this study is toassess the impact of music therapy on stress levels and burnout risk on the operating room staff. This is a pre-experimental study including the operating rooms staff of urology and maxillofacial surgery in the academic hospital of Sahloul Sousse (Tunisia) over a period of six weeks. The study consisted of three phases. The first was an initial assessment of stress level with a predefined survey. The second included three music therapy sessions per day over one month. The third was an immediate stress level reassessment following the intervention. Stress levels were evaluated using the Perceived Stress Scale version PSS-10 and the Maslach Burnout Inventory. The overall response rate was 73.9%.The average age of the study population was 37.8 ± 7.7 years with a female predominance (64.7%). After the music therapy program, Perceived Stress Scale average score decreased from 22 ± 8.9 to 16 ± 7.9 (p = 0.006). Concerning the burnout, only the average score of emotional exhaustion decreased significantly from 27 ± 10.8 to 19.2 ± 9.5 (p = 0.004). Music therapy is an innovative approach that seems to reduce operating theatre staff stress. It must be considered as a non pharmacological, simple, economic and non invasive preventive tool.